NVESTIGATE THE RELATIONSHIP BETWEEN UNSYSTEMATIC RISK AND PROFIT GROWTH OF ACCEPTED COMPANIES IN TEHRAN STOCK EXCHANGE (Singaporean Journal of Business Economics and Management, 2014)
Unsystematic risk includes most important issues in financial management, because unsystematic risk has received little attention in Iran. Profitability of a company as well as non-systematic risk assessment criteria requires different conditions in order to be timely, reliable, accurate picture of the company. In this study we have tried to switch the relationship between risk and unsystematic growth of accepted companies in Tehran Stock Exchange during the years 85 to 89 are discussed. In this study, the growth of dividends includes net profits, gross profit and operating profit is intended. The sample consists of 146 firms operating in the resource cement vehicles and parts, chemicals, machinery and significantly under medication is used to analyze the data of 7 risk unsystematic and growth dividends in companies active in industries thereis such significant relation.